Inclusive Primary Schools in Sweden: Case Studies - MENTEL Klaudyna; BUJNIEWICZ Zbyszko (Architecture, Civil Engineering, Environment, 2025)
In Sweden, 90.8% of students are educated in inclusive schools. According to data from the European Agency for Special Needs and Inclusive Education, 85.53% of children diagnosed with special educational needs, including those with an autism spectrum diagnosis, attend general inclusive primary schools. The aim of this study is to identify features of the school environment that may influence the functioning of students with autism spectrum disorder (ASD) in primary education. A multiple case study was carried out using an expert-based method that included the analysis of written descriptions, photographs, and architectural documentation. Based on a comprehensive review of the literature, specific design criteria were identified as potentially beneficial for supporting students on the autism spectrum. The selected design criteria – spatial zoning based on sensory stimulus exposure, delineation of integration and activity zones, and the sequencing of functional areas – are applied in selected inclusive schools in Sweden. The results show that the school environments are structured by zoning spaces according to the level of sensory stimulation, with dedicated low-stimulation areas clearly marked. The schools use partitions with different levels of transparency and organize zones based on the type of activity. These are arranged in a sequence that reflects the daily school schedule. Functional spaces are logically organized, and the presence of clear sightlines and visual landmarks helps students navigate and understand the layout of the school more easily. The study illustrates how these criteria can be implemented in both the architectural and organizational design of educational environments. Designing school in alignment with these spatial principles may enhance the daily functioning and educational participation of students on the autism spectrum.